The American GI Forum : in pursuit of the dream, 1948-1983 - Ramos, Henry A. J., 1959- (Arte Público Press, 1998)
A history of the American GI Forum, a civil rights group formed by Hispanic servicemen and women in response to the intolerable conditions they found in their communities upon their return from World War II; covering the years between 1948 and 1983.